Women, English and Empowerment: Voices from Rural Bangladesh - Rahman, Sayeedur (Script Journal: Journal of Linguistic and English Teaching, 2017)
English has been an integral part of Bangladesh education system since her independence in 1971. The process of globalization has transformed the lives of million in the developing world like Bangladesh.Â  The rise of globalization has also meant a growing awareness of the use of English and its possible impact on the lives of people. However, there has not been adequate research conducted which could find a direct link between English and empowerment. The role of English and its impact on the socio-economic growth of individuals didnât get much attention. Moreover, there has been inadequate attention to understanding of the relationship between English and its role on womenâs empowerment in rural community. With this background this study is an attempt to contribute to our understanding of the socio-economic orientation of women by analyzing the impact of English in Bangladesh through a qualitative approach. It provides a useful understanding of the need for English language in specific areas of work. Based on such needs, it will attempt to provide insights for the planning of sustainable intervention strategies for the development of English language skills for women in Bangladesh.